Efektivitas Reformasi Agraria Melalui Program Pendaftaran Tanah Sistematis Lengkap di Kabupaten Bintan - Yana, Wily; Muhammad, Adji Suradji; Edison, Edison (Jurnal Ilmu Administrasi Negara (JUAN), 2020)
The systematic land-plating program is the first silmutaneous action of land registration of all land objects across the republic of Indonesia in one rural region or another similar name, which included the collecting and verifying of physical data and jurisdictional data regarding one or several land registration items for the purposes of registration.The pupose of this reseach is to know the effectiveness of agrarian reintegration through this programme. The inerl program began to carry out the star review iin 2017, but it has not been effective since there are still people who complain that they have not received a certificate from the existing program, and the four inflection gauges are just one indicator with the result. The objective of the lending program to increase land refistration in order to reduce land disputes and orderly administration of land and also to give legal assurance and protection to the owner of a land.